Women’s Right of Inheritance in Islam: Between the Sharia Provision and Demand of Socio-cultural Changes - Mohd Anuar Ramli; Muhammad Ikhlas Rosele; Adang Darmawan Achmad; Hudzaifah Achmad Qotadah (UIN Sunan Gunung Djati, 2023)
Women’s inheritance is a never-ending issue. This issue has been frequently debated amongst academician, especially involving distribution of women’s inheritance, which is half of what men received. This polemic arises due to the changes in social system of Muslim society, which is now different than the early time of wahy (revelation) conveyance. This is due to the distribution ratio of 2:1 is already seen unreasonable, though still to be seen in the context of Islamic law and the fundamentals in determining this law. Hence, this article will focus on the polemic of women inheritance from the perspective of Islamic law to determine whether the men to women ratio of 2:1 is rigid, or whether there are other areas that place women before men. This article also discusses how far this right can change and the alternative solution to the issue in the context of current Islamic society. A descriptive qualitative approach was adopted with the primary data obtained through several relevant sources. Data analysis was carried out using a legal approach, a sociological approach, and a philosophical approach. This study concluded that with better education, more women have career and they also contribute to the family economy. This scenario has changed the marriage landscape. In other words, women no longer involve in a narrow domestic space; they are even capable to be alongside men in the public sphere. In accordance with this phenomenon, demand exists for equal inheritance right between man (son) and woman (daughter). Nevertheless, not all Islamic law can be changed due to the changes in the society sociocultural.